MATHEMATICAL MODELING OF UNSTABLE FILTRATION FOR GAS DEPOSITS - Sergey Evgen’evitch Abramkin; Sergei Evgen’evich Dushin; Ivan Mitrofanovich Pershin; Daniil Dmitrievich Sirota (Современная наука и инновации, 2022)
The paper presents mathematical models of steady and unsteady isothermal gas filtration. For the case of pressure distribution in the bottomhole formation zone around a single well, a numerical model of gas filtration is constructed that approximates the boundary value problem by an implicit four-point scheme by the sweep method, assuming that the density and viscosity of the gas are constant, the permeability and elastic capacity of the rock. The presented model allows to calculate and predict the change in the pressure distribution in the area around the well.